CCS ROADMAP FOR PORTUGAL: CO2 TRANSPORT AND STORAGE OPTIONS AND RISKS - Carneiro, Júlio (2016)
This report constitutes Deliverable 1 of the approved proposal CCS roadmap for Portugal - WORK PLAN, as of 24 November 2013. Deliverable 1 attempts to clarify the options and risks for CO2 transport and geological storage in Portugal. Previous CCS studies in Portugal, namely the FP7 COMET project and the nationally funded KTEJO project, have conducted site screening for storage locations and defined the most economic pipeline corridors. However, those projects have focused solely on the technical and economic issues. No discussion of the existing alternatives was made and risks associated to those alternatives have not been identified. This report aims at clarifying the following issues:  Are there geological conditions in Portugal for safe and permanent CO2 storage? What is the location and capacity of potential storage sites? What are the risks and costs involved?  What is the best option for CO2 transport in the country? What are the risks and costs involved? Is there a role for transport by ship?  What activities may have conflicting interests or gain from synergies with the implementation of CO2 storage? Answer to these questions and this report are provided as a technical background to sub-task 1.1scenarios of role and need for CCS - sub-task 1.3- economic impact and business opportunities - as well as for task 2 - Communication Process – of the CCS roadmap for Portugal, phase I.